Akurasi hasil terjemahan manual book bahasa Mandarin ke dalam bahasa Indonesia melalui mesin terjemahan otomatis - Irawan, Reynald Satria Dwiky; Delijar, Ressi Maulidina (Universitas Mulawarman, 2024)
There are so many conveniences that can be accessed in this sophisticated era, such as the convenience of automatically translating Chinese text into Indonesian. However, the accuracy and precision of the translation results obtained from the automatic translation machine still need to be reviewed further. This research aims to identify language errors in the translation of Chinese documents into Indonesian through Youdao Fanyi and DeepL Translator. This research is descriptive qualitative research based on language error analysis. The source used is taken from the manual book of an e-cigarette company, as much as one document consisting of several Excel cells. The Chinese document was translated into Indonesian using two automatic translation machines. The translation results were analyzed for language errors at the morphological, syntactic and semantic levels. The results of this research show that there are still language errors at the morphological, syntactic and semantic levels in the translated texts produced by Youdao Fanyi and DeepL Translator. Both automatic translation engines tend to translate texts word by word and don’t recognize terminology related to machinery and engineering terms. The translation results are an initial form of translation that needs to be edited to obtain more accurate document translation results.